127k views
1 vote
=Solve this system of equations byusing the elimination method.4x + 2y = -6-3x – 2y = 7([?], []-=The ordered pair of solutionsis written in the format (x, y).

=Solve this system of equations byusing the elimination method.4x + 2y = -6-3x – 2y-example-1

1 Answer

2 votes

STEP - BY - STEP EXPLANATION

What to find?

The solution to the system of equations.

Given:

4x + 2y = -6

-3x – 2y = 7

To solve the given system using the elimination method, we will follow the steps below:

Step 1

Eliminate y by adding the first and second equation.


\lparen4x-3x)+\left(2y-2y\right)=-6+7
x=1

Step 2

Substitute x=1 into the first equation.


4\left(1\right)+2y=-6

Step 3

Subtract 4 from both-side of the equation.


\begin{gathered} 2y=-6-4 \\ \\ 2y=-10 \end{gathered}

Step 4

Divide both-side of the equation by 2


(2y)/(2)=-(10)/(2)
y=-5

Therefore, the solution in its ordered pair is (1, -5)

User Robert Petz
by
4.4k points